Avaliação do Programa Nacional de Suplementação de Ferro em um município da Bahia - Almeida, Samila Nathalia Bispo de (2014)
The Iron-Deficiency Anemia (FA) has high prevalence in Brazil being associated with low birth weight, growth retardation, cognitive impairment and lower resistance to infections in children, and increased perinatal mortality in pregnant women. In response to this problem the National Program of Iron Supplementation (NPIS) created tools to record, evaluate and monitoring regularly and permanently, the process of establishing and implementing the three levels of the National Health System management and their results, forming what is called Management Module, which is nothing more than its Information System (IS). This article aimed to perform a descriptive and critique analysis of this system performance using as research outline the generation and use of data at the municipal level. The retrospective design used as the primary data interviews with health professionals, managers and users of the program, and as a secondary material, SI PNSF data and reports from the General Commission of Food and Nutrition, the state and municipal management, among other documents. The quality and relevance of the information was analyzed through the categories: completeness, reliability, timeliness, access, correction of goals and consistency of the information with the goals of health politics. Despite the SI have easily accessible data, the results showed errors in setting national goals and program coverage, in addition to wrong data input by local coordinators. Accessibility was also affected, disallowing the use of data for decision making at the local, intermediate and national levels. Finally, there was serious planning problems arising, at least in part, the institutional culture that underpins health practices and maintains the information as secret or as political and bureaucratic power resource. Studies and interventions towards the clearing and settlement of these issues could contribute to the improvement of health information systems, and in particular the PNSF, so as to allow the control and reduction of iron deficiency anemia in children and pregnant Brazilian women.